Czech Republic : 2008 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Czech Republic. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
Growth in the Czech Republic is projected to slow sharply in 2009 amid a gathering recession abroad and tightening credit at home. This 2008 Article IV Consultation highlights that the shrinking demand from the euro area, especially Germany, will curtail exports and direct investment inflows. Executive Directors have praised the generally strong fundamentals that have helped the Czech economy weather the initial spillover effects of the global financial crisis relatively well. Directors have supported the Czech National Bank's recent decisions to cut the policy interest rate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet